Linguistic skills and the intergenerational transmission of language - Ramón Caminal; Lorenzo Cappellari; Antonio Di Paolo (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2018)
We investigate the pattern of intergenerational transmission of language in a bilingual society. We consider the case of Catalonia, where the two main speech communities, Spanish and Catalan, are of similar sizes, both languages are official, and each one enjoys the protection of a different layer of government. However, whereas all native Catalan speakers are bilingual, only a fraction of native Spanish speakers are fully proficient in Catalan. In this environment, transmission decisions are far from trivial. We provide a simple theory showing that changing the costs of acquiring a second language affects language skills as well as the language parents speak to their children. Empirically, we exploit the natural experiment generated by a language-in-education reform that introduced Catalan-Spanish bilingualism at school to estimate the causal effects of language skills on intergenerational transmission. Results show that the increased proficiency in Catalan among native Spanish speakers induced by the reform augmented their propensity to speak Catalan to their offspring. The causal effect of the policy-induced increase in language proficiency on language transmission is not confounded by spurious trends, potential changes in language identity, and linguistically mixed partnership formation.
Keywords: I28; J13; J24; J62; Z13; 330; language; intergenerational transmission; language proficiency; language-ineducation reform